Review Literatur: Dampak Perubahan Iklim terhadap Satwa Liar - Marsudi, Sundari; Ifanda, Dayun; Tambunan, Hardiansyah; Silalahi, Hanna Tresia; Arinda, Dela (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Climate change is one of the most significant global threats to the survival of wildlife, particularly in tropical regions that harbor high biodiversity yet remain vulnerable to environmental pressures. This study aims to examine the impacts of climate change on the distribution, phenology, behavior, and physiological responses of wildlife through a literature review of 23 scientific articles published between 2015 and 2025. The findings indicate that species with narrow habitat ranges and high sensitivity to temperature are especially vulnerable to climate change, particularly when compounded by anthropogenic disturbances such as deforestation and habitat fragmentation. Various impacts of climate change have been identified in tropical wildlife. Montane forest-endemic birds in the Andes have shifted to higher elevations due to rising temperatures, while Southeast Asian amphibians are threatened by declining microhabitat humidity. Changes in reproductive rhythms are evident in African wild dogs (Lycaon pictus), which have experienced shifts in their birthing seasons. In addition, increased nocturnal activity has been observed in large mammals in Africa and Asia as a response to thermal stress. Adaptive conservation strategies discussed include the establishment of ecological corridors, habitat restoration, and species distribution modeling. A science-based conservation approach is essential to address future ecological challenges.